The Effectiveness of Using Bingo Games Media to Improve Students Vocabulary Mastery - Mohamad Farhan Syukron; Yon A E (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The purpose of this study was to determine the effectiveness of using bingo games media to improve students vocabulary mastery at MTsN CIBINONG. Based on the theory of Groller, Bingo is often played simultaneously by large groups; the winner being the first contestant is to cover a line of five numbered spaces on his card as selected by chance and announced by the game caller. Design used in this study is experimental quantitative research. The research subject were 30 students at MTsN 3 CIBINONG. The result of using vocabulary Bingo games strategy showed that the students were interested in teaching and learning English. Based on the fact, it is underlined that in this study, the hypothesis of this study is accepted and well proven; as the writer has previously hypothesized that there is a significant difference between teaching vocabulary to the students of MTsN CIBINONG who are taught vocabulary by using Bingo Game and those are taught without using Bingo Game. The students of MTsN CIBINONG are interested in studying vocabulary through Bingo Game. The students enjoy learning vocabulary by using Bingo Game. The students of MTsN CIBINONG who are taught vocabulary by using Bingo Game get higher score than those who are taught without using Bingo Game. There is a significant difference between control group and experimental groups. From the statistical analysis, it is found that the students of experimental group who are taught vocabulary by using Bingo Game gained better result than the students of controlled group who are taught without using Bingo Game.